Hybrid Intelligent Water Drops Algorithm For Examination Timetabling Problem - Bashar A.Aldeeb; Mohammed Azmi Al-Betar; Norita Md Norwawi; Khalid A.Alissa; Mutasem K.Alsmadi; Ayman A.Hazaymeh; Malek Alzaqebah (Science Direct, 2024)
Indexed by Scopus